Is Continuous Monitoring of Skin Surface Temperature a Reliable Proxy to Assess the Thermoregulatory Response in Endurance Horses During Field Exercise? - Verdegaal, Elisabeth-Lidwien J. M. M.; Howarth, Gordon S.; McWhorter, Todd J.; Delesalle, Catherine J. G. (Frontiers in Veterinary Science, 2022)
Hyperthermia is a performance and welfare issue for exercising horses. The thermoregulatory stressors associated with exercise have typically been estimated by responses in the laboratory. However, monitoring surface skin temperature (Tsk) coincident with core temperature (Tc) has not previously been investigated in horses exercising in the field. We investigated the suitability of monitoring surface Tsk, as a metric of the thermoregulatory response, and simultaneously investigated its relationship with Tc using gastrointestinal (GI) temperature. We evaluated Tsk in 13 endurance horses competing during four endurance rides over 40 km (n=1) or a total of 80 km (n=12) distance. Following each 40 km loop, horses were rested for 60 minutes. Tsk and Tc were continuously recorded every 15 seconds by an infrared thermistor sensor located in a modified belt and by telemetric GI pill, respectively, and expressed as mean ± SD. Net area under the curve (AUC) was calculated to estimate the thermoregulatory response to thermal load of Tsk over time (°C x minutes) using the trapezoidal method. The relationship between Tsk and Tc was assessed using scatterplots, paired t-test or generalized linear model ANOVA (delta Tsk) (n = 8). Ambient temperature ranged from 6.7 - 18.4°C. No relationship was found between Tsk and Tc profiles during exercise and recovery periods, and no significant difference between delta Tsk results was detected when comparing exercise and rest. However, time to maximum Tsk (67 minutes) was significantly reduced compared to Tc (139 minutes) (p = 0.0004) with a significantly lesser maximum Tsk (30.3°C) than Tc (39.0°C) (p = 0.0002) during exercise. Net AUC Tsk was 1164 ± 1448 and -305 ± 388°C x minutes during periods of exercise and recovery, respectively. We conclude that Tsk monitoring does not provide a reliable proxy for the thermoregulatory response and horse welfare, most probably because many factors can modulate Tsk without directly affecting Tc. Those factors such as weather conditions, applicable to all field studies, can influence the results of Tsk in endurance horses. The study also reveals important inter-individual differences in Tsk and Tc time profiles, emphasizing the importance of an individualized model of temperature monitoring.